Under the Mupundu Tree - Strategies for Hope (FB Productions, 2015)
Volunteers in home care for people with HIV/AIDS and TB in Zambia’s Copperbelt. How a home care programme involving over 500 volunteers from local churches has successfully integrated TB control into home care for people with HIV. Produced by FB Productions for the Strategies for Hope Trust.
Free